2020
DOI: 10.5539/jsd.v13n1p97
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pathway for Agricultural Labour Adaptation in a Vietnamese Village under the Context of Revonation

Abstract: The revival of family farming with rural out migration has undisputable contribution for household livelihoods. This paper aimed to figure out the relationship between migration and agricultural labour adaptation in Vietnamese rural areas. Based on qualitative and quantitative analysis, this study showed that migration had complicated impacts on labour management intra-household for sustaining agricultural activities, there is no remarkable agricultural labour deficit created due to internal migration in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Land 2021, 10, 117 2 of 17 Domestic units in rural areas which are facing the constraints of a context of renovation try to implement multiple pathways as job alternatives. A Vietnamese study concluded that the rural population continues to choose both on-farm and off-farm jobs to overcome the constraints of socio-economic changes [9]. Off-farm or on-farm job alternatives do not automatically represent self-employment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Land 2021, 10, 117 2 of 17 Domestic units in rural areas which are facing the constraints of a context of renovation try to implement multiple pathways as job alternatives. A Vietnamese study concluded that the rural population continues to choose both on-farm and off-farm jobs to overcome the constraints of socio-economic changes [9]. Off-farm or on-farm job alternatives do not automatically represent self-employment.…”
Section: Introductionmentioning
confidence: 99%
“…There is a high risk of impeding a holistic approach by creating artificial boundaries [17]. On the one hand, off-farm employment is supposed to be abundant in urban areas and the surrounding zone, even if job-seekers live in or come from rural areas, especially in the agricultural sector [9]. On the other hand, rural areas are continuously being converted into urban zones as the Rwandan "master plan" of land use is supposed to be updated every five years.…”
Section: Introductionmentioning
confidence: 99%